Giant Anteater Population Density Estimation and Viability Analysis Through Motion-Sensitive Camera Records - Bertassoni, Alessandra; Bianchi, Rita de Cassia [UNESP]; Desbiez, Arnaud Leonard Jean (Wiley, 2021)
Giant anteater (Myrmecophaga tridactyla) populations are decreasing throughout their range. We tested a methodology for individual identification using camera records and fur patterns to estimate the giant anteater population in a protected area of the Brazilian Cerrado. We identified 9 adult individuals and successfully modeled population abundance and density. Our models estimated an adult population of 16.8 (range = 15–19) giant anteaters through a mark-resight approach and 12.5 individuals (range = 9.7–25.5) through a spatially explicit capture-recapture approach. Density estimates were 0.3–0.4 animals/km2. Using these estimates, we performed a population viability analysis to understand and predict this population's future. We modeled scenarios without direct effects and models simulating a double carrying capacity and the supplementation and removal of individuals. Even in the more optimistic scenarios, the population is predicted to decreases over time, with ≤8 individuals remaining in 100 years. Given the study area surroundings, realistic models include removals of giant anteaters in the population. Identification of giant anteaters using cameras can inspire conservationists to acquire population data throughout its distribution and obtain population trends to evaluate the species' conservation status. Individual identification of giant anteaters using a motion-sensitive camera design is feasible, opens new avenues for population analyses, and allows the study of population trends in difficult regions. © 2021 The Wildlife Society.
Keywords: abundance; camera; Cerrado; density; giant anteater; Myrmecophaga tridactyla; population; SECR; spatially explicit capture-recapture